2010
DOI: 10.1001/archgenpsychiatry.2010.111
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Depression During Pregnancy and the Risk of Preterm Birth, Low Birth Weight, and Intrauterine Growth Restriction

Abstract: Context Maternal depressive symptoms during pregnancy have been reported in some, but not all, studies to be associated with an increased risk of preterm birth (PTB), low birth weight (LBW), and intrauterine growth restriction (IUGR). Objective To estimate the risk of PTB, LBW, and IUGR associated with antenatal depression. Data Sources and Study Selection We searched for English-language and non–English-language articles via the MEDLINE, PsycINFO, CINAHL, Social Work Abstracts, Social Services Abstracts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
1,117
11
37

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,598 publications
(1,224 citation statements)
references
References 160 publications
(206 reference statements)
59
1,117
11
37
Order By: Relevance
“…Depression itself has been shown to be associated with a number of adverse pregnancy outcomes, such as spontaneous abortion, fetal death, low birth weight, and preterm birth (Bonari et al, 2004;Grote et al, 2010). In our study, over 50% of venlafaxineexposed mothers reported using the medication during the entire early pregnancy period, which suggests longterm treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Depression itself has been shown to be associated with a number of adverse pregnancy outcomes, such as spontaneous abortion, fetal death, low birth weight, and preterm birth (Bonari et al, 2004;Grote et al, 2010). In our study, over 50% of venlafaxineexposed mothers reported using the medication during the entire early pregnancy period, which suggests longterm treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Other perinatal complications arising from mild to clinically relevant symptoms of prenatal maternal stress, depression or anxiety can include premature delivery and low birth weight of the child [118][119][120]. There were also indications that depression in the mother can predispose to intrauterine growth retardation [121][122]. If maternal mental health problems remain untreated, there is a risk that these symptoms will continue even after the birth of the child [123][124], which can seriously limit the maternal care given to the infant and the interaction between mother and infant [125][126][127].…”
Section: Effects Of Stress Depression and Anxiety In Pregnancymentioning
confidence: 99%
“…[1][2][3] Although treatment is essential, the use of antidepressant medication during pregnancy has been found to be lower than other times of the life cycle. 4 One of the contributing factors for poor uptake of pharmacologic interventions appears to be concerns regarding the safety of antidepressant exposure for the fetus.…”
mentioning
confidence: 99%
“…However, the warnings suggested a direct conflict between safety of the fetus and a mother's need for antidepressant medication, perhaps without regard to the documented negative effects of untreated depression on pregnancy outcomes. 3,7 The results of prior meta-analyses have been conflicting. Several have found no evidence of increased risk of major congenital malformations above the baseline [8][9][10] rate, which has been widely cited as 1%-3% for any pregnancy in North America [11][12][13][14] and less than 4% for minor congenital malformations.…”
mentioning
confidence: 99%